Geophysics learning transformation: Assessment Of The Need For Technology-Based Learning Media And Environmental Issues - Thariq, Abd. Mun’im; Hamsu Abdul Gani; Darmawang (Cita konsultindo, 2025)
This research aims to analyze the need for the development of geophysics learning media in universities, especially in the context of relevance to technological developments and environmental issues. The method used is quantitative descriptive with data collection techniques through observation and distribution of questionnaires to lecturers and students at two universities that hold geophysics courses. The results of the study show that learning outcomes at both campuses still focus on basic competencies, such as understanding geophysical concepts, practicum skills, and field data analysis. However, new competencies related to the application of technology such as artificial intelligence (AI), machine learning, and big data have not been explicitly accommodated. In terms of learning media, the use of reference books dominated (40%), followed by presentation slides (27%), learning videos (20%), and teaching aids (13%), which showed the tendency to use conventional media. In addition, the integration of geophysics learning materials with environmental issues is still low, with only 33% integrated and 67% not integrated. These findings show the need for the development of geophysics learning media that is more interactive, contextual, and adaptive to technological developments and global challenges. This research provides an important basis for curriculum innovation and the development of learning media that support 21st century learning outcomes.